The Big Smoke : congestion charging and the environment - Banister, D (Edward Elgar, 2008)
This book chapter is from Road congestion pricing in Europe : implications for the United States: In February 2003, the London Congestion Charging Scheme was introduced and in 2006 a similar policy was introduced in Stockholm. In both cases automobile traffic entering the cordon declined by about 20 percent. This book evaluates these and other similar programs exploring their implications for the United States. This study’s value lies in the fact that it examines road pricing in the real world and not simply from a theoretical viewpoint. As a comparative study it will appeal to both policymakers and academics in transportation economics and planning, urban economics, planning and economic geography.